Artikel Uji toksisitas akut oral xilooligosakarida dari hidrolisis xilan jerami menggunakan enzim rekombinan Endo-β-1,4-D-Xylanase : Studi Toksisitas Xilooligosakarida - Vergian, Putra; stri Ratnadewi, Anak Agung I; Riandy, Cahyaningtyas Tetta; Rukmana, Riesma; Ulfa, Evi Umayah; Siswoyo, Tri Agus; Syafriadi, Mei (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2026)
Xylooligosaccharides (XOS) are recognized as prebiotics that stimulate the proliferation of probiotic bacteria and enhance short-chain fatty acid (SCFA) production. Compared to other prebiotics, XOS offer notable advantages, including thermal stability and tolerance to a broad pH range. Building on these attributes, this study aimed to evaluate the potential toxicity of XOS derived from rice straw xylan hydrolyzed using recombinant endo-β-1,4-D-xylanase expressed in Saccharomyces cerevisiae. Acute oral toxicity was assessed in male Wistar rats at a single dose of 2000 mg/kg body weight, with observations conducted over a 14-day period. Parameters evaluated included body weight, clinical signs, hematological and biochemical indices, as well as macroscopic and histopathological alterations. Signs of toxicity were observed as changes in stool consistency within the first 4 to 24 hours, while mortality occurred in three male rats. Although body weight showed a tendency to increase, particularly in males, the estimated LD₅₀ value ranged between >500 and 2000 mg/kg body weight, classifying XOS as moderately toxic. Moreover, histopathological examination revealed pathological alterations in the kidneys and liver, while serum biochemical analysis indicated metabolic changes that remained within normal limits. Overall, these findings suggest that XOS possess promising prebiotic potential; however, further studies are required to confirm their long-term safety for application in food products.